2019
DOI: 10.1007/s00520-019-05228-8
|View full text |Cite
|
Sign up to set email alerts
|

The importance of and satisfaction with sex life among breast cancer survivors in comparison with healthy female controls and women with mental depression or arterial hypertension: results from the Finnish nationwide HeSSup cohort study

Abstract: Introduction Breast cancer (BC) and its treatment is associated with several physical and psychosocial changes that may influence sexuality for years after treatment. Women with BC show significantly greater rates of sexual dysfunction than do healthy women. The purpose of the study was to evaluate how a BC diagnosis associates with women's perceived sexuality and sexual satisfaction. Material and methods The data of the ongoing prospective Health and Social Support (HeSSup) survey was linked with national hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The findings of this systematic review illustrate the experience of changes in sexual well-being and spousal relationship as well as the barriers of seeking professional help to address their sexual intimacy issues among the Chinese adults living with cancer. In line with previous studies in other population groups (Mütsch et al, 2019;Reese et al, 2017;Salakari et al, 2020), our review indicated that Chinese adults experience many challenges throughout the cancer care trajectory and identify the unaddressed sexual supportive care needs of adults who are living with cancer. Improving sexual intimacy issues for cancer survivors may be critical to alleviating the tension of the spousal relationship and ensuring optimal therapeutic outcomes.…”
Section: Discussionsupporting
confidence: 83%
“…The findings of this systematic review illustrate the experience of changes in sexual well-being and spousal relationship as well as the barriers of seeking professional help to address their sexual intimacy issues among the Chinese adults living with cancer. In line with previous studies in other population groups (Mütsch et al, 2019;Reese et al, 2017;Salakari et al, 2020), our review indicated that Chinese adults experience many challenges throughout the cancer care trajectory and identify the unaddressed sexual supportive care needs of adults who are living with cancer. Improving sexual intimacy issues for cancer survivors may be critical to alleviating the tension of the spousal relationship and ensuring optimal therapeutic outcomes.…”
Section: Discussionsupporting
confidence: 83%
“…Satisfaction in one's sex life can be a critical issue for the quality of life in breast cancer patients and should be included in individual patient assessment. Sexual dysfunction is more frequently observed in patients with breast cancer than in healthy women, and treatment-related adverse effects can have a prolonged, social negative impact (29). With these factors in mind, sexual satisfaction in breast cancer survivors deserves more attention, particularly in pre/peri-menopausal patients (30).…”
Section: Distress Body Image Self-esteem and Sexualitymentioning
confidence: 99%
“…Preserving the skin, nipple, and areola might increase the possibility of residual cancer tissues and increase the risk of recurrence, which has been a concern of researchers. A recent study showed that MRM with skin nipple-areola preservation combined with stage I prosthesis reconstruction was a safe and effective surgical method and would not increase the local recurrence rate or distant metastasis rate [7]. Local recurrence of breast cancer is mainly derived from the mammary gland's residual ductal epithelium, not the skin tissues of the breast [6].…”
Section: Discussionmentioning
confidence: 99%
“…Still, how to improve the patients' quality of life after treatments is now a significant challenge [3]. Breast preservation can significantly improve the quality of life of women after breast surgery [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%